Optimising hydrogen carrier pathways for industrial decarbonisation: a techno-policy framework for readiness in infrastructure and governance - Nnabuife, Somtochukwu Godfrey; Yang, Jinyan; Kuang, Boyu; Akpala-Okoroafor, Eunice Ngozi; Onwualu, Peter Azikiwe (Elsevier, 2025)
Industrial decarbonisation is a major route to net-zero emissions, and hydrogen is emerging as a key energy carrier for hard-to-abate sectors. This work applies a techno-policy readiness framework which encompasses infrastructure compatibility, regulatory institutional alignment, technological readiness, and market readiness, to improve hydrogen carrier pathways for industrial purposes. The framework uses comparative assessments of production routes, transport and storage pathways, and policy instruments to assess the techno-economic performance and governance readiness to support each hydrogen carrier pathway. The findings indicate that ammonia and liquid organic hydrogen carriers (LOHCs) have the highest readiness for long distance transportation, while compressed hydrogen and liquid hydrogen can still be used for shorter distances or niche markets. The analysis also indicated that successful hydrogen rollout will depend as much upon governance and infrastructure alignment, and not only on technical readiness. Overall, this research provides realistic pathways for policymakers and industry actors to expedite their hydrogen uptake into industrial systems, and ultimately enable a quicker transition to global decarbonisation goals.
Keywords: Hydrogen carrier; Industrial sectors; Hydrogen storage; Hydrogen transport; Hydrogen infrastructure; Technological barriers; 40 Engineering; 34 Chemical Sciences; Generic health relevance; 7 Affordable and Clean Energy; Energy